Analytical methods to authenticate fats and oils: principles, comparison and application in halal food products - Roslan, Raihanah; Tukiran, Nur Azira (Malaysian Analytical Sciences Society, 2024)
Fats and oils, commonly used in food products, are highly susceptible to adulteration, where their originality and quality can be compromised for monetary gain. This paper examines various analytical methods developed to ensure the traceability and verification of the authenticity of fats and oils. The analytical techniques discussed include spectrophotometric methods such as Fourier Transform Infrared Spectrometry (FTIR), Nuclear Magnetic Resonance (NMR), UV-visible (UV-Vis) Spectroscopy, Near-Infrared Spectroscopy (NIR), and Raman Spectroscopy; thermoanalytical methods like Differential Scanning Calorimetry (DSC); and chromatographic techniques including Gas Chromatography-Mass Spectrometry (GC-MS) and High-Performance Liquid Chromatography (HPLC). Data for this paper were collected from a comprehensive analysis of existing literature and studies on the application of these techniques in fat and oil authentication. This paper also includes various chemometric analyses, such as principal component analysis (PCA), cluster analyses, discriminant analysis, and classification analysis, to enhance the interpretation of the analytical results. The advantages and disadvantages of each technique are discussed, along with their underlying principles that facilitate their use in experiments. This paper aims to describe these analytical methods and the related chemometric analyses, emphasising their relevance in both general food safety and the specific context of halal food.